COST AND RETURNS OF PREDOMINANT INTEGRATED FARMING SYSTEMS ADOPTED BY SMALL AND MARGINAL FARMERS IN ADILABAD DISTRICT, TELANGANA - M.H.V. BHAVE, M. SRINIKA, R. VIJAYA KUMARI, K. SUHASINI and (The Journal of Research, PJTSAU, 2019)
An integrated farming system (IFS) is one which focuses on judicious combinations of any one or more of such enterprises and effective recycling of crop residues and wastes for better management of available resources with small and marginal farmers to generate more income and employment for family labourers during off seasons. The decrease in operational land holding, increasing rate of population and declining rate of per capita availability of cultivated land have been major concerns to our nation since the scope for horizontal expansion in farming is limited. Vertical expansion is possible only through adoption of the latest technology, bioengineering and changing of cropping methods to integration of farming systems by putting the components systematically and scientifically in the right order, consuming the least space.